Améliorer la gestion des espaces naturels par la participation. Une analyse du guide français pour l’élaboration des plans de gestion - Angela Osorio; Laurent Schmitt; Dominique Badariotti; Yves Meinard (VertigO, 2023)
Nowadays, environmental protection is a major issue at all scales. In France, as in many countries around the world, one of this field’s key strategy is the protection of natural areas through management and/or restoration measures. Numerous scientific and institutional actors are positioning themselves to propose frameworks to rationalize these management/restoration measures, but these approaches are very rarely the subject of critical scientific analysis. A methodological guide was recently developed to provide coherent guidance to all of those involved in the management of French Protected Natural Areas. We propose here the first scientific evaluation of this guide. It is based on the application of an evaluation framework made up of three criteria: scientific basis, operationality, and legitimacy. These criteria’s application allows us to highlight certain weaknesses within the guide, which are likely to have a negative impact on the quality of the activities led by the managers who use it. We show ways of improving the guide by deploying participatory approaches, which the guide mentions quickly when it should give them greater importance, by explaining the implementation methods and the necessary precautions to be taken in deploying them.